"I Think It's Been Met With a Shrug:" Oncologists' Views Toward and Experiences With Right-to-Try. (3rd September 2020) - Smith, Cambray; Stout, Jeremiah; Adjei, Alex A; Buckner, Jan; Wentworth, Mark; Tilburt, Jon; Master, Zubin
Abstract: Background: The federal Right-to-Try (RTT) Act created an alternate regulatory pathway for preapproval access to investigational drugs. A few studies have examined the experiences of physicians with the Food and Drug Administration's Expanded Access Programs, but to our knowledge, no study has yet to examine their attitudes and experiences toward RTT. Methods: This study explored the views of 21 oncologists at a major cancer center with 3 main sites across the United States using semi-structured interviews and qualitative analysis. Participants were selected to have experience with Expanded Access Programs. Results: Most oncologists had limited familiarity with RTT, and several reported confusion about the legislation, including whether patients have a right to investigational drugs and an obligation for companies to provide them. Although oncologists were interested in decreased regulatory burdens, 3 areas of concern were articulated: lack of safety and oversight, unclear structure and no provision for data collection, and potential heightening of patient expectations. Only 4 oncologists had experience discussing RTT, and none formally attempted to obtain the drug through this mechanism. Participants questioned the practicality of RTT legislation and suggested alternative ways to improve access. Conclusions: The study provides foundational empirical data underlying challenging ambiguities by experienced oncologists familiar with off-trial use of investigational therapeutics and reaffirms the role of physicians and regulatory bodies in mitigating the risks of investigational drugs. Our findings highlight the need for medical centers to inform oncologists about RTT and other preapproval pathways so that they are able to address questions from patients interested in nontrial investigational drugs.